A Maximum Spreading Speed for Magnetopause Reconnection. Issue 11 (5th June 2018) - Walsh, B. M.; Welling, D. T.; Zou, Y.; Nishimura, Y.
Abstract: Past observations and numerical modeling find magnetic reconnection to initiate at a localized region and then spread along a current sheet. The rate of spreading has been proposed to be controlled by a number of mechanisms based on the properties within the boundary. At the Earth's magnetopause the spreading speed is also limited by the speed at which a shocked solar wind front can move along the magnetopause boundary. The speed at which a purely north to south rotational discontinuity propagates through the magnetosheath and contacts the magnetopause is measured here using the Block‐Adaptive‐Tree Solar Wind Roe‐Type Upwind Scheme global magnetohydrodynamics model. The propagation speed along the magnetopause is fastest near the nose of the magnetopause and decreases with distance from the subsolar point. The average propagation speed along the dayside magnetopause is 847 km/s. This is significantly larger than observed rates of reconnection spreading at the magnetopause of 30–40 km/s indicating that, for the observed conditions, the speed of front propagation along the magnetopause does not limit or control the spreading rate of reconnection. Plain Language Summary: Energy can transfer from the Sun to the Earth's space environment at varying rates. The results found here dismiss one model that could control the rate of energy change or magnetic reconnection at the edge of the Earth's magnetic field. Key Points: Solar wind fronts can spread across the magnetopause at over 850 km/s The speed of solar wind structures contacting the magnetopause does not limit the spreading of magnetic reconnection under typical conditions